Short-term isolation effects on the brain, cognitive performance, and sleep—The role of exercise - Klein, Timo; Braunsmann, Leonard; Koschate, Jessica; Hoffmann, Uwe; Foitschik, Tina; Krieger, Stephanie; Crucian, Brian; Schneider, Stefan; Abeln, Vera (Frontiers in Physiology, 2023)
Isolation is stressful and negatively effects sleep, mood and might also affect the brain in its structure and function. Physical exercise improves brain function. We investigated the influence of physical exercise during isolation on sleep, affect and neurobehavioral function. N=16 were isolated for 30 days with daily exercise routines (ISO100) and n=16 isolated for 45 days with every second day exercise (ISO50). N=27 non-isolated controls either exercised on a daily basis (CTRLEx) or refused from exercise (CTRLNonEx) for 30 days. At the beginning and the end of each intervention intravenous morning cortisol, melatonin, BDNF and IGF-1, positive and negative affect scale, electroencephalography, cognitive function and sleep patterns (actigraphy) were assessed. High levels of cortisol were observed for the isolated groups (p < .05) without negative effects on the brain, cognitive function, sleep and mood after four to six weeks of isolation, where physical exercise was performed regularly. An increase in cortisol, impairments of sleep quality, mood, cognitive function and neurotrophic factors (p < .05 respectively) were observed after four weeks of absence of physical exercise in the CTRLNonEx group. These findings raise the assumption that regular physical exercise routines are a key component during isolation to maintain brain health and function.